Explanatory Model of Self-Efficacy for Cervical Cancer Screening - Angela-Cristina Yanez Corrales; Maria-Teresa Urrutia; Oslando Padilla (Clinical and Experimental Obstetrics & Gynecology)
Background: Cervical cancer (CC) screening is a public health concern, and social conditions partially explain the individual’s ability to respond to the preventive aspect of the disease. This study aims to design an explanatory model of self-efficacy (SE) for CC screening. Methods: This study was conducted on 969 women aged 25–64 years who used the public health care system in Santiago, Chile. Multiple linear regression analysis was conducted to generate the explanatory model for global SE index and for each of their components as function of sociodemographic factors, factors related to interaction with the health system, risk factors for CC, family functioning, and the knowledge and beliefs of women regarding the disease and its prevention. Results: The factors that explain high levels of SE are low levels of education and knowledge of the risk factors of CC, better beliefs about the barriers to and benefits of a Papanicolaou (Pap) test, participation in breast cancer screening, and highly functional family Apgar. Conclusions: To administer as many CC screening as possible, achieve effective interventions, and reach optimal coverage rates, it is necessary to consider social determinants, collaborate with other cancer screening programs, and work toward the beliefs of the population.